Small intestinal hemangioma: A case report - Beraldo, Rodrigo Fedatto [UNESP]; Marcondes, Mariana Barros [UNESP]; da Silva, Daniel Luiz [UNESP]; Grillo, Thais Gagno [UNESP]; Baima, Julio Pinheiro [UNESP]; de Barros, Jaqueline Ribeiro [UNESP]; Quera, Rodrigo; Saad-Hossne, Rogério [UNESP]; Sassaki, Ligia Yukie [UNESP] (International Scientific Information, 2021)
Objective: Background: Case Report: Conclusions: Rare disease Hemangiomas are benign vascular neoplasms that originate from fast-growing embryonic mesodermal tissue and have a proliferation of endothelial cells, which manifest themselves in different forms, locations, and di-mensions. Owing to its rarity and similarity of symptoms with other chronic bowel diseases, intestinal hem-angioma is a differential diagnosis to be considered in patients presenting with symptoms such as abdominal pain and anemia. A 46-year-old woman with a history of diffuse abdominal pain and abdominal distension for 20 years presented with a worsening of symptoms in the past year. She denied weight loss or changes in bowel habits or stool appearance. Laboratory investigations showed microcytic hypochromic anemia. Colonoscopy results were nor-mal. A contrast-enhanced abdominal computed tomography scan showed focal and concentric thickening of the small intestine, measuring 8.3 cm, and associated with calcifications, intestinal dilation, mesenteric lymph node enlargement, and vascular dilatation and consistent with infectious granulomatous diseases such as intestinal tuberculosis, carcinoid tumor, Crohn’s disease, and lymphoma. The tuberculin skin test resulted in a strong 25-mm reaction. We suspected intestinal tuberculosis or expansive injury, and the patient underwent exploratory laparotomy with visualization of a 4-to 5-cm bluish/blackish vegetating lesion located 220 cm from the Treitz angle. The anatomopathological study showed cavernous hemangioma of the small intestine, measuring 2.6×1.0 cm. The patient recovered well and remained asymptomatic. Although rare, intestinal hemangioma should be on the list of differential diagnoses for chronic intestinal dis-eases, especially if there is anemia due to coexisting iron deficiency.
Keywords: Crohn disease; Diagnosis, differential; Hemangioma, cavernous; Inflammatory bowel diseases